2019
DOI: 10.1016/j.jpag.2018.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Adnexal Torsion in Children and Adolescents: A Retrospective Review of 245 Cases at a Single Institution

Abstract: a b s t r a c tStudy Objective: Adnexal torsion (AT) requires urgent surgical intervention to preserve ovarian function. Historically, treatment for AT was oophorectomy because of concerns related to leaving a nonviable ischemic ovary. No published studies support these theoretical concerns and current literature supports conservative management. The aim of this study was to review the institutional outcomes for AT cases, including salvage rates and complications. Design, Setting, Participants, Interventions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 42 publications
1
29
1
Order By: Relevance
“…This trend, however, appears to be reversing. A more recent retrospective review published in 2019 of 245 cases of ovarian torsion showed that 94% had laparoscopic surgery and 95% had ovarian preservation …”
Section: Managementmentioning
confidence: 99%
“…This trend, however, appears to be reversing. A more recent retrospective review published in 2019 of 245 cases of ovarian torsion showed that 94% had laparoscopic surgery and 95% had ovarian preservation …”
Section: Managementmentioning
confidence: 99%
“…Although typically occurring in postmenarchal females, ovarian torsion has been documented in younger patients. 1,2 In infants, the ovaries are typically found in the lower abdomen as opposed to the pelvis in adolescents, which is possibly why this pathology was discovered in our patient. 3 Ovarian torsion often occurs due to the presence of benign or malignant masses 5 cm in size or larger, although no mass was identified in our patient.…”
Section: Discussionmentioning
confidence: 65%
“…3 Ovarian torsion often occurs due to the presence of benign or malignant masses 5 cm in size or larger, although no mass was identified in our patient. 1 No one physical complaint is highly sensitive or specific, and abdominal pain is intermittent only 57% of the time. 1,2 Figure 1 The left ovary (LO) is enlarged to 3.3 Â 1.8 Â 1.5 cm (4.6 mL) and there are multiple follicles present.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to previous reports with ovary-sparing procedures performed in 40 to even 95% of the cases with benign conditions. 10,[20][21] The high rate of oophorectomies in this patient group is partly explained by our earlier policy to prefer oophorectomy to avoid tumor rupture also in benign neoplasms. We have started to be more active in performing ovary-sparing procedures nowadays since good long term results have been observed with ovary-sparing surgery in pediatric patients despite black-bluish color in twisted ovary.…”
Section: Accepted Articlementioning
confidence: 87%